2015
DOI: 10.15850/amj.v2n4.656
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Body Mass Index and Age at Menarche

Abstract: Background: The decline of age at menarche has been reported in several countries, it occurred because of genetic, ethnic, and socioeconomic improvement in nutritional status and environment. The improvement of nutritional status has occurred globally all over the world including in Indonesia. One of the measuring tools in nutritional status is body mass index (BMI). The objective of the study was to assess the correlation between BMI and age at menarche. Methods: A cross-sectional study was carried out among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…research in Sumedang showed that there was no correlation between age at menarche and BMI. 22 The hypothesis of Frisch and McArthur states that there is a critical fat mass to trigger the first menstruation and more fat mass to maintain reproductive capacity, but this has not been proven in several studies. 23 The national survey conducted by Batubara et al also concluded that most Indonesian adolescents will experience menarche in the age range of 12-14 years (mean 12.96 years) if BMI is included in the 50 th percentile or more.…”
Section: Discussionmentioning
confidence: 99%
“…research in Sumedang showed that there was no correlation between age at menarche and BMI. 22 The hypothesis of Frisch and McArthur states that there is a critical fat mass to trigger the first menstruation and more fat mass to maintain reproductive capacity, but this has not been proven in several studies. 23 The national survey conducted by Batubara et al also concluded that most Indonesian adolescents will experience menarche in the age range of 12-14 years (mean 12.96 years) if BMI is included in the 50 th percentile or more.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Sebaliknya, penelitian di Sumedang menunjukkan bahwa tidak ada korelasi antara usia menarche dan IMT. 22 Hipotesis Frisch dan McArthur menyatakan bahwa terdapat massa lemak kritis untuk memicu terjadinya menstruasi pertama dan massa lemak yang lebih untuk mempertahankan kapasitas reproduksi, namun hal ini belum terbukti pada beberapa penelitian. 23 Survei nasional yang dilakukan Batubara dkk juga menyimpulkan bahwa sebagian besar remaja Indonesia akan mengalami menarche pada rentang usia 12-14 tahun (rerata 12,96 tahun) jika IMT termasuk pada persentil ke-50 atau lebih.…”
Section: Pembahasanunclassified